Efficiency, Merit and Privilege: Public Administration Reforms in Brazil and Turkey - Akkoyunlu, Karabekir (Revista do Serviço Público, 2021)
The Brazilian and Turkish public administrations display a mixture of patrimonial, traditional bureaucratic and managerial characteristics. This patchwork is a result of more than a century of disjointed reform attempts to address chronic institutional problems such as government inefficiency, political patronage and corruption. Based on a comparative study of the two cases using official data, reports and a review of the public administration literature, this paper analyses the historical evolution and present structures of the civil service in Brazil and Turkey. Both public administrations continue to face diverse sets of challenges today, albeit in different forms and degrees: government inefficiency comes across as a major problem in Brazil, while the deterioration of the merit principle is particularly disconcerting in Turkey. Public sector employees enjoy more limited rights and benefits in Turkey compared to Brazil, where the civil service is faced with the opposite charge of undue privilege in a highly unequal society. Finally, while corruption and political patronage remain problematic in both cases, their causes appear to be different.